Effect of low-shrinkage monomers on the physicochemical properties of experimental composite resin. Issue 1 (1st January 2018) - He, Jingwei; Garoushi, Sufyan; Vallittu, Pekka K.; Lassila, Lippo
Abstract: This study was conducted to determine whether novel experimental low-shrinkage dimethacrylate co-monomers could provide low polymerization shrinkage composites without sacrifice to degree of conversion, and mechanical properties of the composites. Experimental composites were prepared by mixing 28.6 wt% of bisphenol-A-glycidyl dimethacrylate based resin matrix ( bis -GMA) with various weight-fractions of co-monomers; tricyclo decanedimethanol dacrylate (SR833s) and isobornyl acrylate (IBOA) to 71.4 wt% of particulate-fillers. A composite based on bis -GMA/TEGDMA (triethylene glycol dimethacrylate) was used as a control. Fracture toughness and flexural strength were determined for each experimental material following international standards. Degree of monomer-conversion (DC%) was determined by FTIR spectrometry. The volumetric shrinkage in percent was calculated as a buoyancy change in distilled water by means of the Archimedes' principle. Polymerization shrinkage-strain and -stress of the specimens were measured using the strain-gage technique and tensilometer, respectively with respect to time. Statistical analysis revealed that control group had the highest double-bond conversion ( p  < .05) among the experimental resins tested. All of the experimental composite resins had comparable flexural strength, modulus, and fracture toughness ( p  > .05). Volumetric shrinkage and shrinkage stress decreased with increasing IBOA concentration. Replacing TEGDMA with SR833s and IBOA can decrease the volumetric shrinkage, shrinkage strain, and shrinkage stress of composite resins without affecting the mechanical properties. However, the degree of conversion was also decreased.